Dynamics of the monetary sector of Ukraine during the war and its impact on the efficiency of the banking system - Dziamulych, Mykola; Krupka, Mykhailo; Stashchuk, Olena; Korobchuk, Tetiana; Mostovenko, Nataliia; Avramchuk, Lidiia; Chyzh, Nataliia; Tur, Oleksandr (AD ALTA, 2024)
The article examines the dynamics of indicators of Ukraine’s monetary sector after the beginning of the war and determines its impact on the efficiency of the functioning of banking institutions. The peculiarities of the use of currency and financial instruments by commercial banks of Ukraine in the conditions of destabilization of the banking sector due to the destructive influence of Russian aggression are considered. The dynamics of bank clients’ transactions with foreign currency and the volume of interventions of the National Bank of Ukraine in the foreign exchange market since the beginning of the war were studied. The problems of commercial banks with attracting deposits to ensure the efficiency of operational activities are identified. An analysis of the dynamics of the index of rates for deposits of individuals, as well as the yield of bonds of the domestic state loan, as the main instruments for attracting funds in Ukraine’s financial market, was carried out.
Keywords: foreign exchange market; financial instruments; banking sector; deposits; government bonds; G 18; E 52